High-dose neutron irradiation of beryllium and titanium beryllide: Summary and outlook - Vladimir Chakin; Rolf Rolli; Hans-Christian Schneider; Ramil Gaisin; Pavel Vladimirov; Michael Klimenkov; Michael Duerrschnabel; Nikolai Zimber; Michael Rieth; Bronislava Gorr; Francisco A. Hernández; Dirk Radloff; et al. (Nuclear Materials and Energy)
The irradiation experiment conducted in the HFR material testing reactor, under conditions simulating the operating environment of the DEMO breeding blanket, along with subsequent post-irradiation examinations (PIEs) of irradiated beryllium-based materials—such as pure beryllium and titanium beryllide—enabled a comparative analysis of their radiation resistance for potential use as neutron multipliers. The PIEs clearly demonstrated the superiority of titanium beryllide over beryllium, particularly in terms of reduced swelling, lower tritium retention, and enhanced mechanical properties at elevated temperatures. As a result, titanium beryllide blocks have been proposed to replace beryllium pebbles in the Helium-Cooled Pebble Bed (HCPB) DEMO breeding blanket design. A production technology for fabricating titanium beryllide blocks was successfully developed, and further advancements in this technology, along with research on full-scale blocks, have been outlined.